Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.nepr.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

‘Living the rural experience-preparation for practice’: The future proofing of sustainable rural midwifery practice through midwifery education

Abstract: Rural practice presents unique challenges and skill requirements for midwives. New Zealand and Scotland face similar challenges in sustaining a rural midwifery workforce. This paper draws from an international multi-centre study exploring rural midwifery to focus on the education needs of student midwives within pre-registration midwifery programmes in order to determine appropriate preparation for rural practice. The mixed-methods study was conducted with 222 midwives working in rural areas in New Zealand (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This is in accordance with the findings of Jefford and Jomeen [44], who report that independent midwives in the UK spoke of feeling ‘out on a limb’ and of ‘being blamed’ for women’s refusals, and of Symon et al [40], who found that hospitals did not respect holistic midwives’ expertise. This theme of difficulty working with other providers in the chain of maternity care can also be found in the work of Kensington et al [45] and Crowther and Smythe [46] among midwives in rural practices in New Zealand and Scotland. In addition, as Crowther et al found, in case of a bad outcome, midwives can fear the notoriety that may accompany being identified as the midwife who ‘was responsible for’ a dead baby [47].…”
Section: Discussionmentioning
confidence: 82%
“…This is in accordance with the findings of Jefford and Jomeen [44], who report that independent midwives in the UK spoke of feeling ‘out on a limb’ and of ‘being blamed’ for women’s refusals, and of Symon et al [40], who found that hospitals did not respect holistic midwives’ expertise. This theme of difficulty working with other providers in the chain of maternity care can also be found in the work of Kensington et al [45] and Crowther and Smythe [46] among midwives in rural practices in New Zealand and Scotland. In addition, as Crowther et al found, in case of a bad outcome, midwives can fear the notoriety that may accompany being identified as the midwife who ‘was responsible for’ a dead baby [47].…”
Section: Discussionmentioning
confidence: 82%
“…Studies from other health professions have outlined the influence of various factors on graduate work location, [9][10][11][12][13][14][15] whilst this study additionally focuses on the subjective influences on workplace choice. To the authors' best knowledge, this is the first study to examine these factors concerning paramedicine in Australia and seeks to illustrate the juxtaposition of factors between paramedicine and other health professions.…”
Section: Resultsmentioning
confidence: 99%
“…Studies from health professions other than paramedicine have outlined the influence of various factors on graduate work location. The literature reports strong evidence for the positive impact of rural background, 9,10 rural education, 11,12 rural placements 11,13,14 and mentorship 9,15 towards promoting rural practice amongst medical, nursing and allied health graduates. In one Australian study, allied health graduates of rural origin were 2.4 times more likely to be practising in a rural location one year after graduating than those of a metropolitan background 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The research team reached a consensus on the final template of themes following three faceto-face meetings and regular virtual meetings. These themes have been reported on elsewhere (Crowther et al, 2019;Kensington et al, 2018). Subsequently, two regional focused articles have been written, the first specifically focusing on the Scottish rural midwives' data (Crowther et al, 2020) and this article, which focuses specifically on the New Zealand rural midwives' data.…”
Section: Discussionmentioning
confidence: 98%